Prenatal vitamin D levels and child wheeze and asthma. (1st February 2021) - Adams, Sarah N.; Adgent, Margaret A.; Gebretsadik, Tebeb; Hartman, Terryl J.; Vereen, Shanda; Ortiz, Christina; Tylavsky, Frances A.; Carroll, Kecia N.
Abstract: Background: Maternal vitamin D status during pregnancy may influence lung development and risk of childhood wheeze and asthma. We investigated the relationship between prenatal vitamin D and child asthma in a racially diverse cohort with a high burden of vitamin D insufficiency and child asthma. Materials and methods: We included mother–child dyads in the prenatal Conditions Affecting Neurocognitive Development and Learning in Early Childhood (CANDLE) cohort (2006–2011, Shelby County, Tennessee). Maternal plasma vitamin D [25(OH)D] was measured from second trimester ( n  = 1091) and delivery specimens ( n  = 907). At age 4–6 years, we obtained parent report of current child wheeze (symptoms within the past 12 months) and asthma (physician diagnosis and/or medication or symptoms within the past 12 months). We used multivariable logistic regression to assess associations of 25(OH)D and child wheeze/asthma, including an interaction term for maternal race. Results: Median second trimester 25(OH)D levels were 25.1 and 19.1 ng/ml in White ( n  = 366) and Black women ( N  = 725), respectively. We detected significant interactions by maternal race for second-trimester plasma 25(OH)D and child current wheeze ( p = .014) and asthma ( p = .011). Odds of current wheeze and asthma decreased with increasing 25(OH)D in dyads with White mothers and increased in dyads with Black mothers, e.g. adjusted odds ratio (95% confidence interval) for asthma: 0.63 (0.36–1.09) and 1.41 (1.01–1.97) per interquartile range (15–27 ng/ml 25[OH]D) increase, respectively. At delivery, protective associations in White dyads were attenuated. Conclusion: We detected effect modification by maternal race in associations between prenatal 25(OH)D and child wheeze/asthma. Further research in racially diverse populations is needed.